TESTING THE INFORMATION SYSTEM SOFTWARE USING BEHAVIOR DRIVEN DEVELOPMENT METHOD - RIZWAN, Ucu Nugraha; RIZWAN, Siti Atikah Nurduha Robaiah; RIZWAN, Djoko Rospinoedji (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The testing phase is the stage that determines whether the software is in accordance with user requirements or not. The testing phase does not fully guarantee the quality of the software made but it can give more confidence to its users. In reality, during development, there were so many obstacles that resulted in the application not being maximally tested. Behaviour Driven Development (BDD) is a set of practices in agile software development that is designed to assist teams in building and delivering software that has more value, quality and speed. BDD can encourage collaboration between project team members and business teams, where all test scenarios are written in non-technical language that can be understood by all stakeholders. The purpose of this research is to implement BDD which is integrated with automation testing tools in a software development. Tools used in this research are Cucumber and Katalon Studio. With this research, testing is expected to be carried out more quickly and can bring all stakeholders, both technical and non-technical parties, into one table that is used to share knowledge about the system and testing requirements